Reform and its complexities in modern Britain essays inspired by Sir Brian Harrison - Kinzer, Bruce L. 1948-; Kramer, Molly Baer 1968-; Trainor, Rick 1948- (Oxford University Press, 2022)
The essays in this volume, taken together, span the era of British history from 1780 to the present that has engrossed the attention of Brian Harrison in a career of more than 50 years. In keeping with his diverse interests, they vary widely in subject matter. Yet each contributes, in some fashion, to an appreciation of the complexities of reform in modern Britain. Throughout his career Harrison has demonstrated an unwavering interest in social movements and pressure groups. He has analysed the organisation of reform movements and their bases of support; explored the aspirations and beliefs motivating individuals to start or join such movements; and examined the ideas and ideals shaping their conception of human improvement
This edition also issued in print: 2022. - Includes bibliographical references and index
Keywords: Geschichte 1780-2000; Public administration / Great Britain / History; Social movements / Great Britain / History; Political sociology / Great Britain / History; Reform; Great Britain / Politics and government; Großbritannien; Aufsatzsammlung